Antimicrobial Resistance Surveillance Systems: Are Potential Biases Taken into Account? - Olivia Rempel; Johann DD. Pitout; Kevin B. Laupland (Canadian Journal of Infectious Diseases and Medical Microbiology)
The objective of this study was to assess potential biases that may influence the validity of contemporary antimicrobial-resistant (AMR) pathogen surveillance systems. Although surveillance data have been widely published and used by researchers and decision makers, little attention has been devoted to the assessment of their validity. A Medline search was used to identify reports, in 2008, of laboratory-based AMR surveillance systems. Identified surveillance systems were appraised for six different types of bias. Scores were assigned as ‘2’ (good), ‘1’ (fair) and ‘0’ (poor) for each bias. The results of this assessment indicate that there are several potential biases that can influence the validity of AMR surveillance information and, therefore, the potential for bias should be considered in the interpretation and use of AMR surveillance data.